Faktor - Faktor Yang Berhubungan Dengan Rendahnya Minat Ibu Dalam Menggunakan KB Implant Di Desa Talikumain Wilayah Kerja Puskesmas Tambusai Kabupaten Rokan Hulu - Nurcahaya Hasibuan, Syafnely, (Jurnal Martenity and Neonatal, 2014)
Implants are a levonorgestral contraceptives containing silastic capsules wrapped in silicon (polydimethylsiloxane) and placed under the skin. In Indonesia, Women who use birth implants as much as 71 838 people (9.78%). The purpose of this study is known factors - factors related tomother's lack of interest in selecting the implant as a contraceptive in PHC Tambusai Year 2013 Rokan Hulu analytic research method with a cross-sectional design. The way the sampling is done by simple random sampling that is all that using contraception. The data was collected using aquestionnaire distributed to mothers who use contraceptives. Analysis of research data using Chi Square test. On the degree of confidence (CI) 95% is obtained maternal age factor p value = 0.753, p value = 0.002 knowledge, education p value = 1.000 and p value = 0.001 parity. The conclusion of this study showed that there was no significant association between maternal age and education with the use of implants in PHC Tambusai KB Rokan Hulu in 2014 and there was a significant relationship between maternal parity with the knowledge and use of family planning health centersTambusai implants in Rokan Hulu in 2014. Midwives are expected to advise the IEC on improving knowledge and parity for women taking contraceptives, so that mothers can use the birth implants.